Total Preputial Flap: A Reliable and Versatile Technique for Urethral and Penile Reconstruction - Ludwikowski, Barbara; González, Ricardo (Frontiers in Pediatrics, 2014)
Abstract. We revisit the technique of total preputial flap (TPF) and its application for urethroplasty, penile skin coverage of both and present our results in 43 patients. (41 hypospadias, 2 epispadias). There were no instances of flap necrosis. In patients without prior attempts at reconstruction (n=36) we observed 4 urethro-cutaneous fistulas. TPF allowed the repair of cases of proximal hypospadias in one stage with an acceptable complication rate.